A comparative study of thyroid stimulating hormone among lean and obese women with polycystic ovarian syndrome - C., Sangeetha M.; Patil, Suman Shivanagouda; Arunkumar, Nalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The polycystic ovarian syndrome (PCOS) is an abnormality of young women of reproductive age. Between 20-50% of women with PCOS are normal weight or thin, and the pathophysiology of the disorder in these women may be related to a hypothalamic-pituitary defect that results in increased release of LH. PCOS and Thyroid disorders share certain common characteristics, risk factors, and pathophysiological abnormalities. In this study we have compared the serum TSH levels in obese and non-obese PCOS women to detect if there is a significant difference in the occurrence of hypothyroidism based on the BMI. Methods: Non-pregnant women attending the gynecological OPD diagnosed with PCOS as per Rotterdam criteria were included. Serum TSH was done in all women diagnosed as PCOS and based on their BMI women were either included in obese or non-obese group using Asian cut-off for BMI and the values compared. Results: In the present study 152 women were included. Women with low BMI and normal BMI were grouped as lean PCOS or non-obese PCOS and the overweight and obese women together were grouped as obese PCOS. The total number in the lean group was 28 and 124 in the obese group. Raised serum TSH levels were observed in 23.02%(35) women out of which 17.14%(6) belonged to the non-obese group and the remaining 82.85%(29) to the obese group. Among the 152 women thyroid enlargement was seen in 1.3%(2). Both women had raised serum TSH levels and both belonged to the obese group. Conclusions: The results of our study seem to indicate that thyroid dysfunction in PCOS women developed irrespective of presence or absence of obesity.